Hormonal changes causing rhinitis in pregnancy among Malaysian women - Indirani, B.; Raman, R.; Omar, Siti Zawiah (Cambridge University Press, 2013)
Objectives: To investigate the aetiology of rhinitis occurring in pregnancy, by (1) describing the relationship between pregnancy rhinitis and serum oestrogen, progesterone, placental growth hormone and insulin-like growth factor, and (2) assessing the prevalence of pregnancy rhinitis among Malaysian women. Methods: Prospective study involving 30 pregnant women followed at an ante-natal clinic for 14 months. Hormone levels were analysed during pregnancy and the post-partum period. Results: Levels of all four hormones were elevated in the third trimester, compared with first trimester and postpartum values. Rhinitis patients had higher levels of oestrogen and insulin-like growth factor 1 in the third trimester than non-rhinitis patients, although these differences were not statistically significant. The prevalence of rhinitis was 53.3 per cent, with most cases occurring in the third trimester. Patients with pregnancy rhinitis had a higher prevalence of female babies, compared with non-rhinitis patients (p = 0.003). Conclusions: Pregnancy rhinitis was significantly more common in women giving birth to female babies. Women with pregnancy rhinitis had a non-significant elevation in oestrogen and insulin-like growth factor 1 levels, compared with those without rhinitis.